Toma de decisiones financieras en los estudiantes de la Universidad del Azuay. Enfoques de la Teoría de las Finanzas y la Prospectiva del Comportamiento - Ladrón de Guevara Cortes, Rogelio; Orellana Osorio, Iván Felipe; Tonon Ordóñez, Luis Bernardo (UDA AKADEM, 2024)
Las finanzas conductuales se analizan desde el punto de vista de la psicología porque la racionalidad de los individuos en la toma de decisiones incluye las emociones, el género y su educación. Algunos organismos internacionales han advertido que es necesario mejorar la educación financiera de las personas para que puedan tomar buenas decisiones. Por ello, se realizó una encuesta a un grupo de estudiantes de la Universidad del Azuay. Los resultados demuestran los efectos de la certeza, la reflexión y el aislamiento en los programas educativos de los participantes del estudio que toman decisiones financieras bajo incertidumbre, basadas en la teoría de la prospectiva, en lugar de la teoría de la utilidad esperada. Los perfiles de riesgo indicaron que las mujeres son más conservadoras que los hombres. Este estudio amplía estudios empíricos previos realizados en universidades de México, Colombia, Brasil y Argentina. Palabras Clave: finanzas conductuales, teoría prospectiva, decisiones financieras, racionalidad y riesgo Abstract Behavioral finance is analyzed from the point of view of psychology because the rationality of individuals in decision-making includes emotions, gender, and education. Some international organizations have warned that it is necessary to improve people’s financial education so that they can make good decisions. A survey was conducted with a group of students from the University of Azuay. Results show that of the study participants who make financial decisions under uncertainty based on the Theory of Prospective rather than Expected Utility Theory, you can see the effects of certainty, reflection, and isolation in the educational programs of these students. Risk profiles also indicated that gender plays a role- women are more conservative than men. This study builds empirical studies that were conducted in the past at universities in Mexico, Colombia, Brazil, and Argentina. Keywords: Pprospect theory, behavioural finance, financial decisions, rationality and risk Abstract Behavioral finance is analyzed from the point of view of psychology because the rationality of individuals in decision-making includes emotions, gender, and education. Some international organizations have warned that it is necessary to improve people’s financial education so that they can make good decisions. A survey was conducted with a group of students from the University of Azuay. Results show that of the study participants who make financial decisions under uncertainty based on the Theory of Prospective rather than Expected Utility Theory, you can see the effects of certainty, reflection, and isolation in the educational programs of these students. Risk profiles also indicated that gender plays a role- women are more conservative than men. This study builds empirical studies that were conducted in the past at universities in Mexico, Colombia, Brazil, and Argentina. Keywords: Pprospect theory, behavioural finance, financial decisions, rationality and risk.